2015
DOI: 10.5367/te.2015.0527
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of financial policy in the hospitality sector in the United States

Abstract: This article investigates the circumstances surrounding large investments by firms in the hospitality sector in the United States. The authors identify 400 large-scale investment events for firms in the restaurant, hotel, and recreation industries. During these events, firms increase their size substantially through building or acquiring assets. The authors determine that a combination of market and firm-specific factors lead to such events. Firms are more likely to engage in large investments when they have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This strategy focuses more on loyalty-based assets, such as technology, franchising and management contracts and less on physical assets such as hotels and restaurants. According to Li and Singal (2019), this strategy reduces risk because it helps corporations to grow and expand; (2) HT companies are characterized by high leverage due to large investments in fixed assets, higher risk and stronger competition compared with other industries and high in capital intensity (Ahmad and Adaoglu, 2018) and (Dewally, et al, 2017);…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…This strategy focuses more on loyalty-based assets, such as technology, franchising and management contracts and less on physical assets such as hotels and restaurants. According to Li and Singal (2019), this strategy reduces risk because it helps corporations to grow and expand; (2) HT companies are characterized by high leverage due to large investments in fixed assets, higher risk and stronger competition compared with other industries and high in capital intensity (Ahmad and Adaoglu, 2018) and (Dewally, et al, 2017);…”
Section: Literature Reviewmentioning
confidence: 99%
“…This means that the US hospitality stocks are sensitive to changes in the monetary policy in general and to changes in interest rates in particular. Dewally et al (2017) have found that hospitality companies prefer to undertake their large investments when the current sales growth is high, market volatility is low or the leverage is low. In the same context, Chen et al (2005) provide evidence that Taiwanese hospitality stocks are affected significantly by economic variables and monetary policy variables.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of works-see, among others, Madan (2007), Jang et al (2008), Dewally, Flaherty, and Shao (2017), Karadeniz, Yilmaz Kandir, Balcilar, and Beyazit Onal (2009), Devesa and Esteban (2011), or Serrasqueiro and Nunes (2014)-have investigated the determinants of hotel firms' debt ratios to discern whether the observed decisions are consistent with the pecking order or the trade-off theory. All these studies report that, empirically, both theories contribute to explaining the observed financing behaviors of hotel firms.…”
Section: Introductionmentioning
confidence: 99%